Combination Antipsychotic Therapies: An Analysis From a Longitudinal Pragmatic Trial. Issue 5 (October 2017) - Foster, Adriana; Buckley, Peter; Lauriello, John; Looney, Stephen; Schooler, Nina
Abstract: Background: Combination antipsychotics (CAs) are prescribed in schizophrenia despite limited evidence of efficacy. To explore the effect of switching from CA to monotherapy, we performed an exploratory analysis of the PROACTIVE (Preventing Relapse in Schizophrenia: Oral Antipsychotics Compared with Injectables: Evaluating Efficacy) study data, in which 305 patients with schizophrenia and schizoaffective disorder were followed for 30 months after randomization to long-acting injectable (LAI) risperidone or second-generation oral antipsychotic (OA). Methods: Patients who entered the PROACTIVE study on CA (n = 50), LAI (n = 20), or OA (n = 206) were compared in terms of time to relapse and clinical measures. Findings: The OA group had significantly fewer hospitalizations than the CA group ( P = 0.009) at baseline. In the CA group, 68% patients relapsed versus 53% in the LAI, and 52% in the OA groups. Although there was no significant difference in the relapse rate among groups on χ 2 test (χ 2 = 3.85, P = 0.146), the log-rank test showed a significant difference among the groups in time to first relapse (χ 2 = 6.81, P = 0.033), with significantly longer time to relapse in the OA group (mean, 562.8 days) than in the CA group (mean, 409.5; P = 0.011). The LAI group's mean time to first relapse (594 days) was not significantly different from the other groups. However, after adjusting for number of hospitalizations, group was no longer significant (hazard ratio, 1.541; P = 0.052). Implications: Based on our exploratory analysis, taking antipsychotic combinations predicts earlier relapse and calls for additional treatment guidance in schizophrenia. Abstract : Supplemental digital content is available in the text.